Medical Management of Open-Angle Glaucoma: Focus on Mechanisms of Action and Adverse Drug Reactions - Norhafiza Razali; Mohammad Daniel Shafiq Hassan; Amy Suzana Abu Bakar; Renu Agarwal (UiTM Press, 2021)
Glaucoma is an optic neuropathy characterised by optic nerve degeneration associated with visual field defects. It remains the world's number one cause of irreversible blindness and patients usually present at late stage of the disease since it is generally asymptomatic until severe. The disease is subdivided into primary and secondary with primary open-angle glaucoma (POAG) being the most common type. At present, lowering the intraocular pressure (IOP) remains the only proven efficient approach in delaying the onset or preventing the progression of the disease. Medical treatment with topical antiglaucoma agents is the treatment of choice in open angle glaucoma. The use of antiglaucoma drugs aims to reduce IOP by enhancing aqueous humour (AH) outflow, reducing AH production, or both. The choice to use any available treatment option should be carefully considered in an attempt to maximise benefits and reducing the risk of developing adverse drug reactions. This review highlights the six classes of ocular hypotensive agents currently in use for POAG treatment including prostaglandin analogues; B-adrenergic receptor blockers; a-2 adrenergic receptor stimulants; carbonic anhydrase inhibitors; muscarinic receptor stimulants; rho kinase inhibitors with regards to their mechanism/s of action and potential adverse drug reactions, and antiglaucoma fixed drug combinations.